Bachelor groups form due to individual choices or environmental disrupters in African striped mice. (December 2021) - Kanyile, Sthandiwe Nomthandazo; Pillay, Neville; Schradin, Carsten
Abstract : In several mammal species, bachelor groups occur as a regular life history stage between dispersal and becoming the breeding male of a multifemale group. How such groups come into existence and how males that choose this strategy differ in life history traits from other males is rarely investigated. Males of the socially flexible African striped mouse, Rhabdomys pumilio, have been historically reported to adopt one of three alternative tactics: small group-living philopatric males, intermediate solitary roaming males or large group-living territorial males. Here, we describe for the first time, bachelors as a fourth male tactic. A long-term study on 13 generations of striped mice revealed two types of bachelor groups: (1) kin bachelor groups formed when all females disappeared, probably due to predation, and (2) nonkin bachelor groups formed by unrelated males that originated from different groups. Whereas kin bachelor groups occurred more frequently during the nonbreeding season, nonkin bachelor groups were most common in the breeding season and had a shorter tenure, since most of these males soon switched to the solitary roaming tactic or the territorial breeder tactic. Importantly, we found that nonkin bachelors were heavier and older than kin bachelors and that they did not differ from solitary roaming males in body mass and age. We therefore identified two different forms of bachelor groups, small kin bachelors whose female group members disappeared and larger nonkin bachelor groups showing traits of an alternative reproductive tactic. Both types of bachelor groups differed in multiple traits, demonstrating that it is important to follow the life histories of individuals to understand the mechanisms leading to alternative tactics. Highlights: We describe bachelor groups as a fourth male tactic in striped mice. Kin bachelor groups form when all females disappear. Nonkin bachelor groups are formed by unrelated males from different groups. Both types of groups differ in body mass, age and seasonality of occurrence.